MEMBANGUN JATI DIRI BANGSA : Globalisasi sebagai Tantangan dan Pancasila sebagai Imperatif Solusi - Moh Mahfud MD (Sabda: Jurnal Kajian Kebudayaan, 2018)
This article commences with a question about the existence of the real characteristics of the nation. The article then explains the nature and culture of Indonesian people as well as the negation of the characteristics of the nation. It also affirms Trisakti and geopolitics as the mosaic of the characteristics, and Pancasila as fundamental to the geopolitics. Furthermore, the article elucidates the present global challenge, mentioning a number of real cases in Indonesia. The writer assesses that the cases are the actual threats towards the sovereignty of the nation. He concludes the article by pointing out three basic measures he is assured of to take the challenge.